Estrada, Oswaldo. La imaginación novelesca. Bernal Díaz entre géneros y épocas. Madrid-Frankfurt Am Main: Iberoamericana- Vervuert, 2009. 207 pp. - Rodríguez-Mansilla, Fernando (2010)
No presenta resumen